Weaving the fabric of shared experience: Immigrant and refugee students engaged in visual Testimonio - Myers, Aimée (Frontiers in Education, 2023)
Testimonio, collective narratives situated within our sociopolitical sphere, is a powerful tool that empowers students and moves them toward a space of collective agency. When multimodalities are added to this process, students can further expand their expression and agency. This article hopes to support educators who want to embed a visual testimonio pedagogy in their own classrooms by exploring ways a secondary teacher sought to develop a critical literacy curriculum with her immigrant students. This article explores the current social discourse on immigrant and migrant students, discusses the foundations of visual testimonio, and offers three tangible examples of classroom activities.